Design and Implementation of High Reliability Space Lighting Equipment - LIU Ming; HOU Zuo-xun; GAO Yuan (Journal of Harbin University of Science and Technology, 2022)
In the manned spaceflight project, LED is used as the light source of the lighting subsystem of the manned spaceflight vehicle for the first time. The application of LED lighting source meets the lighting requirements of astronauts' short-time extravehicular activities in the extravehicular space environment. The space lighting equipment outside the cabin needs to work in a more rigorous and complex space environment, which requires the lighting equipment to have high reliability. In order to solve these problems, the circuit of multiple groups of constant current tubes directly driving the series parallel hybrid LED bulb array is designed, and the aluminum substrate is used as the circuit board substrate to heat the circuit. Meanwhite, the light distribution lens is designed to conduct secondary light distribution for the LED array, making the lighting equipment meet the lighting index requirements. The lighting equipment has passed the environmental tests such as temperature cycling, aging, low-temperature start-up, life test and anti-irradiation total dose test. The lighting equipment is placed 2.5m away from the target for test. The test results show that the illumination field angle of the equipment is greater than 48°, the maximum illumination is 562.5lx, and the illumination uniformity is 56.3%, which meets the requirements of aerospace applications.